Can a Leaflet with Brief Verbal Instruction Teach Nepali Women How to Correctly Contract Their Pelvic Floor Muscles? - Caagbay, Delena-Mae; Black, Kirsten; Dangal, Ganesh; Rayes-Greenow, Camille (Journal of Nepal Health Research Council, 2017)
Background: Pelvic organ prolapse is a common disorder for women in Nepal causing symptoms and reduced quality of life. Pelvic floor muscle exercise is a conservative treatment option for pelvic organ prolapse but the effective way to teach women in Nepal is not known. The objective of this pilot study was to determine if an illustrative leaflet with brief verbal instruction could teach Nepali women to correctly contract their pelvic floor muscles.Methods: Fifteen parous women attending two outpatient gynecology clinics in Kathmandu Valley were interviewed to assess their knowledge of pelvic organ prolapse and pelvic floor muscles exercise. Following verbal instruction and an illustrative leaflet on how to contract their pelvic floor muscles, the transabdominal real time ultrasound was applied to assess the muscle contraction. Results: The median age of 15 participants was 45 years (range 18-75 years) and 10 women had pelvic organ prolapse. Some of the participants (9/15) knew about pelvic organ prolapse but none were aware of the pelvic floor muscles. After being taught how to contract their pelvic floor muscle, only 4 of 14 correctly contracted the pelvic floor muscle. Conclusions: This study highlighted the low knowledge of the pelvic floor muscle, and brief verbal instruction with an illustrative leaflet is also not sufficient in teaching Nepali women how to correctly contract their pelvic floor muscle. Further research is needed to determine how to teach a correct pelvic floor muscle contraction for women with low literacy in resource poor settings.